Explaining changes in educational disparities in competent maternal health care services in urban and rural areas in Ethiopia - Shibre, Gebretsadik; Mekonnen, Wubegzier; Haile Mariam, Damen (Frontiers in Public Health, 2024)
Aggregate statistics of maternal health care services have improved in Ethiopia. Nevertheless, the country has one of the lowest universal health coverage's (UHC) service coverage index, with slight improvement between 2000 and 2019. There accumulate disparity studies using a single dimension of inequality today, but inequality studies combining multiple dimensions of inequality simultaneously may have important policy implications for closing inequalities. In this study, we investigated education inequalities in receipt of maternal health care services in rural and urban areas separately and whether these inequalities decreased, increased, or unchanged.The data for the study came from the 2011 and 2016 Ethiopia Demographic and Health Surveys.Using women's education as a dimension of inequality, we separately analyzed inequalities in maternal health care services in urban and rural settings. Inequalities were measured through the Erreygers concentration index, second differences, and Relative Index of Inequality (RII).Whether or not inequalities changed over time was analyzed by relative and absolute measures.Oaxaca-type decomposition approach was applied to explain changes in absolute disparities over time.There were glaring educational disparities in maternal health care services in urban and rural areas, where the services were more concentrated among women having better schooling. The disparities were more severe in urban than in rural areas. In urban areas, skilled birth service was the most unequal in both periods. Disparities in rural places were roughly similar for all services except that in 2011 postnatal care was the least unequal, and in 2016, skilled birth was the most unequal service. Trend analyses revealed that disparities significantly dropped in urban by absolute and relative measures. Conversely, in rural regions, the disparities grew by the concentration index measure for most services. The RII and second differences presented conflicting results regarding whether the gaps were increasing, shrinking, or remaining the same.Substantial disparities in maternal health care services remained and even increased, as in rural areas. Different and targeted strategies are needed for urban and rural places to close the observed educational inequalities in these areas.